Discovery of the microbiota-gut-brain axis mechanisms of acupuncture for amnestic mild cognitive impairment based on multi-omics analyses: A pilot study - Zi-Han Yin; Qiong-Nan Bao; Ya-Qin Li; Yi-Wei Liu; Zi-Qi Wang; Fang Ye; Xia He; Xin-Yue Zhang; Wan-Qi Zhong; Ke-Xin Wu; Jin Yao; Zi-Wen Chen; et al. (Complementary Therapies in Medicine)
Objectives: Acupuncture is a promising therapy for amnestic mild cognitive impairment (aMCI). Growing evidence suggest that alterations in the microbiota-gut-brain (MGB) axis contribute to the development and progression of aMCI. However, little is known about whether and how acupuncture change the MGB axis of aMCI individuals. Methods: This was a randomized, controlled, clinical trial. Forty patients with aMCI were randomly allocated to either the acupuncture group or the waitlist group. The primary outcome was the change in the Alzheimer’s Disease Assessment Scale-Cognitive Scale (ADAS-Cog) score. In addition, multi-omics was performed to detect changes in brain function, gut microbiota, and serum metabolites. Generalized estimating equations were used to estimate the outcomes, and correlational analyses were performed to explore the relationships between the clinical and multi-omics data. Results: Compared to a mean baseline to week 12 change of –3.94 in the acupuncture group, the mean change in the waitlist group was 1.72 (net difference, –5.66 [95 % CI, –6.98 to –4.35]). Compared to the waitlist group, acupuncture’s MGB axis modulatory effect exhibited altered the regional homogeneity values of Frontal_Med_Orb_L, Cingulum_Mid_L, and Frontal_Sup_Medial_L, relative abundance of gut Ruminococcus_sp_AF43_11 and s_Eubacterium_coprostanoligenes, and levels of serum (11E,15Z)-9,10,13-trihydroxyoctadeca-11,15-dienoic acid, dipropylene glycol dimethyl ether, N6-Me-dA, and DPK, which correlated with changes in ADAS-Cog scores. Conclusions: Our data imply that acupuncture ameliorates overall cognitive function, along with changes in brain activity, gut microbiota, and serum metabolites, providing preliminary evidence of the mechanisms acting through the MGB axis underlying the effects of acupuncture on aMCI.